STRATEGIC EMPHASES AND SUCCESS TOWARDS ORGANIZATIONALLY RESILIENT FILIPINO-CHINESE SCHOOLS - LIM, ESTER (International Journal of Social and Management Studies, 2022)
Abstract: In the face of fast changes in the economy, society, and technology, being resilient is critical to the organization's existence. A highly resilient organization is capable of successfully navigating crises and capitalizing on adversity via change. This study aims to explore on the strategic emphases and measurement of success of Filipino-Chinese schools’ objective to become organizationally resilient. The study used the exploratory research design involving 9 employees: teaching and non-teaching professionals (3), managers and supervisors (3), and administrators (3). An interview guide was used to gather data from the participants. Thematic analysis was applied to process the data. The results show that there are 4 areas that need strategic emphases. These are strategies, leadership, human resource, and services. Additionally, management success can be measured according to the performance of students, employee performance, management performance, and organizational performance in general. The results of this qualitative research will benefit school owners and executives on focus areas relative to making the organization resilient. Keywords: resilience, strategic emphases, measurement of success, Filipino-Chinese schools